Diagnosis and Treatment Modalities of Open Apex – A Review - Ravindranath Megha1 , Newbegin Selvakumar Gold Pearlin Mary2 , Arumugam Karthick3 , Paramasivam Vive (Indian Journal of Forensic Medicine & Toxicology, 2020)
Immature tooth with an open apex is encountered by a clinician from time to time. Proper diagnosis andtreatment planning is necessary to save the tooth and for continued root development. This review is aboutdiagnosis and treatment options available for cases of open apex.